Oxidative stability of sunflower oil flavored by essential oil from Coriandrum sativum L. during accelerated storage. (December 2018) - Wang, Dongying; Fan, Wenchang; Guan, Yifu; Huang, Huina; Yi, Tao; Ji, Junmin
Abstract: The aim of the work was to assess the oxidative stability of sunflower oil flavored by the essential oils extracted of Coriandrum sativum (coriander, CEO) during the accelerated storage of 24 days. In the study, CEO was extracted by Soxhlet apparatus, and its chemical composition was analyzed by gas chromatography with flame ionization detector (GC-FID) and gas chromatography and mass spectrometry (GC-MS), and then, the evaluation for antioxidant effect in vitro displayed that CEO possessed markedly antioxidant potential. Furthermore, after the addition of CEO, acid value (AV), peroxide value (PV), iodine value (IV), p -anisidine value (AnV), thiobarbituric acid reactive substances (TBARS), free fatty acid (FFA), total polar compounds (TPC), tocopherols (TOC) in sunflower oils during the accelerated storage were measured every 4 days, and the results herein exhibited the addition of CEO at 1200 ppm could not only increase the oxidative stability of the sunflower oils, but also exert synergistic effect with TBHQ. Meanwhile, the values of K232 and K268 and fatty acid composition were investigated. The sensory evaluation of the oil samples revealed that the addition of CEO at 1200 ppm could increase aroma flavor and consumers' acceptability, so that it could be developed as convenient condiment. Highlights: The essential oil extracted from coriander was named CEO. CEO could exhibit significant antioxidant effect in vitro. CEO could increase the oxidative stability of sunflower oil during storage. CEO could improve the consumers' acceptance of sunflower oil. Sunflower oil added with CEO was able to be developed as a flavored oil.